Sociodemographic and geographic determinants of childhood immunization coverage and equity in Ghana: Analysis of the 2022 demographic and health survey - Ahlam Tunteeya Saani; Goldfield Edem Azumah (PLoS ONE, 2026)
Background Childhood immunization remains a cornerstone of public health in sub-Saharan Africa, yet substantial gaps in coverage, equity, and schedule adherence persist. This study examines immunization coverage, sociodemographic disparities, predictors of completion, and policy implementation effectiveness in Ghana using nationally representative data. Methods Data from 3,788 children aged 12–35 months in the 2022 Ghana Demographic and Health Survey were analysed using stratified two-stage cluster sampling across 614 enumeration areas. Weighted coverage estimates were calculated for individual vaccines and composite indicators including full immunization, dropout rates, and timeliness. Design-adjusted chi-square tests identified bivariate associations between sociodemographic factors and immunization outcomes. Multivariate logistic regression models incorporated sociodemographic characteristics, healthcare utilization, and information access to identify independent predictors. Equity analysis employed concentration indices, rate ratios, and intersectional stratification. Findings Full immunization coverage reached 69.5% (95% CI: 67.3 to 71.7%), with 25.7% partial immunization and 4.8% zero-dose children. Substantial inequalities emerged across wealth (17.4 percentage point gap), maternal education (18.3 percentage point gap), and region (35.7 percentage point gap). The concentration index of 0.045 indicated modest pro-rich inequality. Dropout rates were concerning, particularly 28.9% attrition between measles-rubella first and second doses among age-eligible children. In adjusted models, facility delivery (aOR=1.43, 95% CI: 1.08 to 1.90), four or more antenatal care visits (aOR=1.55, 95% CI: 1.19 to 2.01), higher wealth (aOR=1.39, 95% CI: 1.04 to 1.87), and maternal secondary or higher education (aOR=1.34, 95% CI: 1.04 to 1.72) independently predicted full immunization. Interpretation Ghana’s immunization program achieves broad initial access but faces critical challenges in retention, timeliness, and equity. Policy priorities should emphasize completion-focused interventions including tracking systems, reminder mechanisms, and targeted outreach to disadvantaged populations.